Analysis of barriers of mHealth adoption in the context of sustainable operational practices in health care supply chains - Swain, Suchismita; Muduli, Kamalakanta; Kumar, Anil; Luthra, Sunil (Emerald, 2024)
Purpose: The goal of this research is to analyse the obstacles to the implementation of mobile health (mHealth) in India and to gain an understanding of the contextual inter-relationships that exist among those obstacles. Design/methodology/approach: A combination of a review of the relevant literature and consultation with subject matter experts is used to identify the barriers to widespread adoption of mHealth. The identified barriers are then analysed using an Interpretive Structural Modelling (ISM) technique to study the interplay existing among them and represent these in a hierarchical manner. Findings: The study explores a total of 15 factors that reduce the efficiency of mHealth adoption in India. The findings of the MICMAC investigation show that the economic situation of the government, concerns regarding the safety of intellectual technologies, and privacy issues are the primary obstacles because of the significant driving power they have in mHealth applications. Practical implications: Promoters of mHealth practices may be able to make better plans if they understand the social barriers and how they affect each other; this leads to easier adoption of these practices. The findings of this study might be helpful for governments of developing nations to produce standards relating to the deployment of mHealth; this will increase the efficiency with which it is adopted. Originality/Contributions: At this time, there is no comprehensive analysis of the factors that influence the adoption of mobile health care with social cognitive theory in developing nations like India. In addition, there is a lack of research in investigating how each of these elements affects the success of mHealth activities and how the others interact with them. Because developed nations learned the value of mHealth practices during the recent pandemic, this study, by investigating the obstacles to the adoption of mHealth and their inter-relationships, makes an important addition to both theory and practice.